Grief Due to Loss of Significant Others: The Role of Social Support, Spiritual Intelligence and Wellbeing-Life Satisfaction - Prapunoto, Susana; Soetjiningsih, Christiana Hari (Kuras Institute, 2024)
Grief can be a disruptive event to one's productivity and well-being. In particular, grief experienced by a close loved one. Especially for individuals who have a strong sense of judgement and local cultural respect such as taboos to convey problems or grief to others. The purpose of this study was to examine the role of social support, spiritual intelligence, wellbeing-life satisfaction on bereavement. The research sample was Javanese people who have a strong tribal culture but experienced the unexpected loss of a close person in Surakarta and Kartasura, Indonesia. Data collection techniques used the Satisfaction with Life Scale (SWLS), Spiritual Intelligence Self Report Inventory (SISRI), Multidimensional Scale of Perceived Social Support (MSPSS), and Pandemic Grief Scale (PGS). Data analysis techniques using quantitative methods with multiple linear regression techniques. The results showed that social support, spiritual intelligence, wellbeing-life satisfaction simultaneously contribute to a person's grieving condition.